PERFECTION OF METHODICAL MAINTENANCE OF DISCIPLINES STUDYING THE INTERACTION OF TRACK AND ROLLING STOCK - Svistunov, V. M. (Science and Transport Progress, 2003)
The questions of the deepenning the student’s knowledge about interaction of the track and the rolling stock are considered in the article. The attention is paid to widening the themes of investigated questions, the development more perfect methods textbooks on the specified subject, the special collection of the problems on the track and the rolling stock interaction, both for student and for degree designing. This will allow to approach near the theory of the questions to their practical decision. The article is intended for scientists, teachers and student of senior course of railway institutes.